2013
DOI: 10.3892/mco.2013.170
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppression involving increased myeloid-derived suppressor cell levels, systemic inflammation and hypoalbuminemia are present in patients with anaplastic thyroid cancer

Abstract: Anaplastic thyroid carcinoma (ATC) is one of the most aggressive neoplasms in humans and myeloid-derived suppressor cells (MDSCs) contribute to the negative regulation of immune responses in the context of cancer and inflammation. In order to investigate the pathophysiology of thyroid cancer, peripheral blood mononuclear cells (PBMCs) were obtained from 49 patients with thyroid cancer, 18 patients with non-cancerous thyroid diseases and 22 healthy volunteers. The MDSC levels were found to be higher in patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 26 publications
5
46
2
Order By: Relevance
“…PTC patients compared with controls, but did show accumulation in patients with anaplastic thyroid cancer (38,39). In contrast, the current study shows significantly higher circulating MDSC levels were observe in a population consisting predominantly of PTC patients.…”
Section: Cd11bcontrasting
confidence: 52%
“…PTC patients compared with controls, but did show accumulation in patients with anaplastic thyroid cancer (38,39). In contrast, the current study shows significantly higher circulating MDSC levels were observe in a population consisting predominantly of PTC patients.…”
Section: Cd11bcontrasting
confidence: 52%
“…88 Peripheral blood MDSC levels were higher in patients with ATC compared to healthy controls and correlated with the serum level of IL-10, thus suggesting a correlation between MDSCs and systemic immunosuppression. 89 The only study investigating the significance of TC-infiltrating MDSCs failed to find an association between MDSC density and patient survival. 90 Indeed, in a wide cohort of histological samples from 398 TC patients (253 PTCs and 13 FTCs) MDSCs were identified as CD11b C and CD33 C cells.…”
Section: Mdscs: Myeloid-derived Suppressor Cellsmentioning
confidence: 99%
“…Accumulating evidence [10][11][12][13] suggests that a population of cells with suppressive activity, referred to as MDSCs, may contribute to the negative regulation of immune responses during cancer and other conditions. We previously characterized circulating levels of MDSCs in patients with various types of malignant diseases and reported that increased production of IL-17 correlated with immune suppression involving MDSCs and with malnutrition in patients with gastrointestinal cancers 2,3,14) . VEGF, previously known as vascular permeability factor, is a 45-kDa protein that belongs to a family of platelet-derived growth factors.…”
Section: Introductionmentioning
confidence: 99%
“…Kazuo Minamikawa 1) , Masahiko Shibata 1,2) , Kenji Gonda 1) , Daisuke Ujiie 1) , Mai Ashizawa 1) , Takahiro Nakajima 1) , Hirokazu Okayama 1) , Wataru Sakamoto 1) , Motonobu Saito 1) , Tomoyuki Momma 1) , Kousaku Mimura 1,2) , Shinji Ohki 1) , Tatsuo Shimura 3) , Hitoshi Ohto 2) , Seiichi Takenoshita 1,2,3) , Koji Kono 1) E [15][16][17]. The biological significance of the different forms of VEGF has yet to be definitively determined.…”
Section: Il-17 and Vegf Are Significantly Associated With Disease Promentioning
confidence: 99%
See 1 more Smart Citation